Aloysisus would accompany about 75 tourists to Ireland to trace Irish- Eastern Canadian ties, reported by Evening Telegram - Mannion,Maura (1985)
As a seasonal traveller and well-informed historian, Aloysius would accompany about 75 tourists from Newfoudland and eastern Canada to Confluence '85 in Waterford, Ireland on June 22-29, 1985. This event was desigened to trace Irish-Eastern Canadian ties. The article reviewed Aloysius's previous travels to Ireland and Aloysius introduced the places where most Irish in Newfoundland were from.